IMPLEMENTASI GAYA KEPEMIMPINAN PADA KINERJA KARYAWAN RESTORAN DAN BANQUET OPERATION PT. HARDAYAWIDYA GRAHA - Muhammad Haqiqi Romadloni; Asyidatur Rosmaniar; Dina Novita (PROCEEDING UMSURABAYA, 2022)
Human resources are the main factor in an organization. In running the company's operations, it takes a leader to organize and lead its operations. This is what underlies that the company is very selective in choosing leaders to direct, encourage, motivate and lead employees in running the company's operations. A leader has a leadership style in carrying out the daily duties that arise from the habits of a leader himself. This research was conducted at the banquet operation and restaurant section of PT. Hardayawidya Graha to determine the implementation of leadership style on the performance of restaurant employees and banquet operation of PT. Hardayawidya Graha. This study uses descriptive qualitative methods by producing qualitative data in words and written sentences. The sampling technique in this study uses the snowball sampling method and the data triangulation method to find a harmonious relationship between the results of interviews, documentation, and observations on the company. This study uses the coding manual analysis method as data analysis. The results show that the Senior Operations Manager of PT implemented the leadership style. Hardayawidya Graha is good and by the theory that experts have put forward. Moreover, the result is strengthened by statements from other informants and documents researchers obtained during PT. Hardayawidya Graha company.Keywords: Implementation of Leadership Style; Employee Performance